(untitled) (Research, Society and Development, 2021)
Introduction: The increase in life expectancy has aroused greater interest in the topic of healthy eating. With this, there is an important increase in the production of specific foods, aimed at maintaining health. This article aims to identify bibliographic productions on the potential benefits of nutraceuticals for the user’s health, describing the knowledge produced on this subject. Methodology: This is an integrative literature review based on bibliographic research. The search strategies allowed the identification of 366 articles in the selected databases. Throughout the analysis of titles and abstract, applying the inclusion criteria, 360 articles were excluded. In total, 06 articles were selected for analysis of the full text that participated in the review on the subject. Using criteria for inclusion and exclusion of articles, after reading and applying the selected criteria, 06 articles were selected for meeting all requirements. Results and discussion: The results show that nutraceuticals have important benefits for the user’s health and that they can be used as a complementary therapy, with the introduction of healthy habits to improve the quality of life. Final considerations: More research should be carried out in order to trace the real benefits of nutraceuticals.